Mission in Question : Anthropology and Evangelization in the Prelature of Ayaviri (1968 - 1975) - Oehri, Noah (2020)
A new approach to —and appreciation of— popular religiosity significantly marked the Latin American Catholic Church in the post-conciliar decades and gave rise to a growing number of anthropological investigations of religious subcultures. However, the reforms of evangelizing practices in response to these studies have thus far aroused little academic interest. This article analyzes the complex relationship between anthropology and mission in the Prelature of Ayaviri (Puno), which, beginning with the Episcopal Conference of Medellín (1968), relied on social-scientific research to reformulate its pastoral practice. Specifically, this article elucidates how the prelature’s renewed engagement with the «other», the Quechua peasant, not only contributed to the knowledge production on the regional socio-religious panorama, but also caused difficulties for a church whose missionary nature was subject to scrutiny and change during the early 1970s.